Size-dependent thermodynamic description of the binary Pb-Sn system. - Gierlotka, Wojciech (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Recently, a new thermodynamic description of the binary Pb – Sn system was proposed and it seems to be interesting to extend this description on the system, where size of particles plays a key-role. To obtain this goal a set of surface Gibbs energies was calculated and added to Gibbs energies describing bulk phases. The extended thermodynamic description was used for calculation of size-dependent phase diagram of binary Pb-Sn system. Comparison of calculation with limited literature information allows for statement that the proposed model is in good agreement with experiment.